Asuhan Keperawatan Menyusui Tidak Efektif Pada Ibu Post Sectio Caesarea : A Case Report - Amellia - Mardhika (Surya : Jurnal Media Komunikasi Ilmu Kesehatan, 2021)
Background: Breast milk is an important component needed by infants to meet nutritional needs and the formation of the baby's immune system. Mothers post sectio caesarea (SC) often experience problems in breastfeeding. Incorrect position and attachment in breastfeeding are the most common causes of delays in breastfeeding.Objectives: To find out the management of nursing care for breastfeeding is not effective in post SC mothers.Design: This research uses a case study approach (case report).Data Sources: In this study, data were obtained through the process of interviews, observation, physical examination, and documentation studies on post sectio caesarea mothers.Results: Nursing care with lactation counseling interventions and breastfeeding education can be applied to post SC mothers according to the expected outcomes, the client's breastfeeding status has improved on the third day. The mother's anxiety decreases, the baby's fussiness is reduced because the baby's attachment to the mother's breast increases, the mother's ability to position the baby correctly increases, the breast milk supply is quite increased, the mother's confidence increases and the baby's suction increases.Conclusions: The implementation of lactation counseling and breastfeeding education can overcome the problem of ineffective breastfeeding and in accordance with the expected outcomes. Lactation counseling and breastfeeding education can be chosen to be carried out according to the condition of the mother in the taking hold phase, it is necessary to form a counselor as the main profession.